2012
DOI: 10.1111/j.1559-1816.2012.00926.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Balanced Risk–Benefit Information and Initial Attitudes on Post‐Information Attitudes1

Abstract: In a realistic social context, people are confronted with both positive and negative information, yet research on this topic is relatively scarce. We present 2 studies examining the role of initial attitudes on the impact of one-sided vs. balanced positive and negative information on attitudes toward food production methods. The first experiment demonstrated that one-sided information influenced postinformation attitudes congruent to the direction of the message content. The second experiment showed that the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
22
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 28 publications
6
22
2
Order By: Relevance
“…An interesting question is what the effect of the name is on the development of attitudes. Previous research has shown that generally the valence of attitudes towards food production technologies remains unaffected when information about the risks and benefits is provided (Fischer, Van Dijk, de Jonge, Rowe, & Frewer, 2013;Frewer, Howard, & Shepherd, 1998;Lusk et al, 2004;Scholderer & Frewer, 2003;Van Dijk, Fischer, De Jonge, Rowe, & Frewer, 2012). On the basis of these findings, the unfavourable initial attitudes towards genomics will be very difficult to change even when information is provided.…”
Section: Subsequent Attitude Developmentmentioning
confidence: 86%
“…An interesting question is what the effect of the name is on the development of attitudes. Previous research has shown that generally the valence of attitudes towards food production technologies remains unaffected when information about the risks and benefits is provided (Fischer, Van Dijk, de Jonge, Rowe, & Frewer, 2013;Frewer, Howard, & Shepherd, 1998;Lusk et al, 2004;Scholderer & Frewer, 2003;Van Dijk, Fischer, De Jonge, Rowe, & Frewer, 2012). On the basis of these findings, the unfavourable initial attitudes towards genomics will be very difficult to change even when information is provided.…”
Section: Subsequent Attitude Developmentmentioning
confidence: 86%
“…There is evidence that individuals seek information that is in line with their current worldview and avoid information that may cause unpleasant feelings or thoughts (Gaspar et al, 2015;Narayan, Case, & Edwards, 2011). In an experimental study, Van Dijk, Fischer, De Jonge, Rowe, & Frewer (2012) found that, following information provision, positive initial attitudes were associated with lower levels of risk perception and higher levels of benefit perception. Initial attitude might also be a proxy for involvement.…”
Section: Initial Attitudementioning
confidence: 94%
“…This in turn has led to an increase in the provision of new information on the risks attached to these food products. This information may elicit feelings of confusion and anxiety, and a need for more information so that individuals can weigh the pros and cons and make well informed decisions on their food intake (Van Dijk, Fischer & Frewer, 2011). Individuals may choose to use the Internet to find additional information (Jacob et al, 2010;Kuttschreuter et al, 2014;Redmond & Griffith, 2006;Tian & Robinson, 2008) which they then process and make sense of, in order to decide whether to purchase and eat the particular products.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations